Em busca da vitória: Futsal Feminino em Parintins - Abreu, Daniel da Costa (Brasil, 2024)
This report, developed from a media product in documentary format, addresses the image of women futsal players in the city of Parintins. The research highlights the lack of investment and adequate infrastructure for the players, revealing a series of challenges they face in the sport. Additionally, it sheds light on the unequal treatment between men and women in sports, reflecting broader issues related to gender and prejudice. By exploring the personal stories of the players, it illustrates the daily difficulties faced and the resilience necessary to continue in the sport despite the adversities.